Some Effects of exchange rate changes - R. Fuerstenberg (Kiel Institute of World Economics (IfW); ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 1979)
When the DM price for one US dollar was quoted at less than two in late February of 1978 this event was reported in the radio news. An extraordinary attention was devoted to this price of a foreign currency at a time when it was changing somewhat more rapidly than it normally does and when it was crossing levels which wise men in Germany thought it would never attain. This particular interest may partly be due to a certain uneasiness about the forces which determine an exchange rate. Since the break down of the Bretton Woods system of fixed exchange rates in 1973 speculation in foreign exchange has become a much harder job than it used to be. There is an enormous demand for reliable forecasts. Many laymen as well as economists hold the view that some version of the purchasing power parity principle determines exchange rates: the relative price of two currencies moves in such a way as to equilibrate the changes in domestic price levels. There is widespread astonishment if this theoretical background - though possibly true in the long run of correctly modified and interpreted - never provides correct forecasts.
Keywords: 330